Yanan Ngurra-ngu Walalja Halls Creek Community Family Programme - Munns, Ailsa (Cambridge Publishing, 2010)
Home-based parent support is an important strategy for assisting parents to develop their parenting confidence and capacity, across a range of physical and psychosocial environments. Social, biological, environmental and family influences during the early years have lifelong impacts on children. The introduction of an Indigenous, peer-led parent support programme in a remote, socially disadvantaged town in Western Australia has allowed the local community to develop culturally appropriate strategies to support their own families. Their anecdotal evidence has demonstrated effective engagement with progrmme visitors with the families, using a partnership approach to promote behaviour and attitudinal changes to parenting.